A gender-responsive approach to designing agricultural risk management bundles - Adhikari, Roshan; Kramer, Berber; Ward, Patrick S.; Foster, Timothy; Sharma, Varun; Gaur, Pushkar; Pattnaik, Subhransu (International Food Policy Research Institute, 2023)
- Bundling agricultural insurance with risk-reducing agricultural technologies can lower the cost of insurance for farmers, but before implementing bundled solutions, it is important to analyze how these bundles would impact men and women differently. -